2019
DOI: 10.3390/medsci7010010
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Respiratory Failure Due to Community-Acquired Pneumonia: A Systematic Review

Abstract: Community-acquired pneumonia (CAP) is a leading cause of mortality worldwide. CAP mortality is driven by the development of sepsis and acute respiratory failure (ARF). We performed a systematic review of the available English literature published in the period 1 January 1997 to 31 August 2017 and focused on ARF in CAP. The database searches identified 189 articles—of these, only 29 were retained for data extraction. Of these 29 articles, 12 addressed ARF in CAP without discussing its ventilatory management, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
3
11
0
1
Order By: Relevance
“…Acute respiratory failure and the development of sepsis are the main causes of CAP mortality. 15 Long-term hypoxia caused by respiratory failure can lead to ischemic changes and dysfunction of the heart, brain, kidney, and lung and may worsen the outcome of CAP and/or lead to higher mortality. 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute respiratory failure and the development of sepsis are the main causes of CAP mortality. 15 Long-term hypoxia caused by respiratory failure can lead to ischemic changes and dysfunction of the heart, brain, kidney, and lung and may worsen the outcome of CAP and/or lead to higher mortality. 16…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Acute respiratory failure and the development of sepsis are the main causes of CAP mortality. 15 Long-term hypoxia caused by respiratory failure can lead to ischemic changes and dysfunction of the heart, brain, kidney, and lung and may worsen the outcome of CAP and/or lead to higher mortality. 16 Almiral et al found that the use of oral steroids and immunosuppressive therapy were clear risk factors for CAP, while the role of cancer was not clear.…”
Section: Model Verificationmentioning
confidence: 99%
“…In one study, the success of NIMV ranged from 20 to 76% and appeared to correlate with the underlying mechanism, with the greatest benefits in patients with hypercapnic COPD or cardiogenic pulmonary edema. 143 Helmet-delivered continuous positive airway pressure was also proven to ameliorate oxygenation in CAP patients with moderate hypoxemic acute respiratory failure. 144 Oxygen therapy by high-flow nasal cannula (HFNC) is a recently developed simple therapeutic option to deliver high fractions of inspired oxygen (FiO 2 ).…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…In the 1980s, the World Health Organization (WHO) developed a case management strategy aiming to reduce deaths from pneumonia (4). While it suggests that in severe pneumonia cases, the cornerstones of management are antibiotic and supportive therapy, the most important basis for the The Effectiveness of Heated Humidified High-flow Nasal Cannula in Children with Severe Bacterial Pneumonia in the Emergency Department DO I: 10.4274/jpr.galenos.2019.15045 management strategy was hypoxemia which is common and potentially associated with increased risk of death (4)(5)(6)(7). Early detection of hypoxemia, and administration of oxygen therapy also improves the outcome of children with SBP (7).…”
Section: Introductionmentioning
confidence: 99%
“…There have been various oxygen treatment options for a long time but these may be insufficient. Heated humidified high-flow nasal cannula (HHHFNC) therapy has recently started to become an alternative oxygen giving method for the treatment of acute RD due to pneumonia (7). HHHFNC can be set up quickly and is a reliable noninvasive respiratory support therapy method (8).…”
Section: Introductionmentioning
confidence: 99%